Fishhooks, fishing spears, and weaving: The bone technology of Madjedbebe, Northern Australia. (3rd February 2023) - Langley, Michelle C.; Wallis, Lynley A.; Nango, May; Djandjomerr, Djaykuk; Nadjamerrek, Clarrie; Djandjul, Raelene; Gamarrawu, Ruth
Abstract: Archeological assemblages of osseous material culture are rare in the Australian context, especially in the north where environmental conditions are not usually conducive to organic preservation. Nevertheless, more than 230 bone artifacts were recovered from the site of Madjedbebe, located in the Mirarr clan estate of the Alligator Rivers region of the Northern Territory. Of these artifacts, 199 have been identified to tool type. Here, we present the analysis of this exceptional assemblage, including the recovery of one‐piece jabbing fishhooks, numerous fishing‐spear tips, fragments of weaving tools, and possible osseous elements originating from ornamental pieces. The size and diversity of the Madjedbebe osseous technology assemblage is unique in the north and provides new insights into the lives of Mirarr peoples over the past 7, 000 years.